Duma w procesie edukacji. Interakcyjna analiza przyczyn i konsekwencji pojawiania się dumy u nauczycieli i uczniów - Pawłowska, Beata (Studia Edukacyjne, 2019)
The aim of the article is to show how pride arises in teachers’ work and students’ learning process. Therefore, school and the education process will be shown through the prism of emergence of one social emotion: pride. In contrast, in some cases, pride is juxtaposed with another social emotion—shame. The emphasis will be placed on pride as the emotion which refers to the diagnosis of social bond and leads to experiencing other emotions such as joy, happiness, satisfaction, etc. It is assumed that frequent experiencing of pride leads to increased self-esteem. I will refer to the concept of Theodore D. Kemper, i.e. a theoretical frame which assumes that emotions arise on the basis of social relations and pride is a result of satisfaction emerging due to the growth of our status. I will moreover invoke the theory of Thomas Scheff, who indicates e.g. that pride as an emotion customizes our behaviors without supervision and control. From a sociological perspective and under an interpretative approach, pride will be treated as a social emotion. The article sums up reflections based on qualitative research conducted by the author in the years 2006-2014.